2005
DOI: 10.1073/pnas.0502521102
|View full text |Cite
|
Sign up to set email alerts
|

Conservation and evolvability in regulatory networks: The evolution of ribosomal regulation in yeast

Abstract: Transcriptional modules of coregulated genes play a key role in regulatory networks. Comparative studies show that modules of coexpressed genes are conserved across taxa. However, little is known about the mechanisms underlying the evolution of module regulation. Here, we explore the evolution of cis-regulatory programs associated with conserved modules by integrating expression profiles for two yeast species and sequence data for a total of 17 fungal genomes. We show that although the cis-elements accompanyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
259
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(282 citation statements)
references
References 35 publications
23
259
0
Order By: Relevance
“…S1) versus their median transcription rate (TR, A-B), total [mRNA] (RA, C-D) and the degradation rate constant (k d , E-F) of their transcriptomes (see 15 other stresses show a positive correlation between TR and GR ( Fig. 2A), rather like that observed under steady-state conditions (see 18 ). On the contrary, the k d profiles show a positive correlation with iGR in all the stress responses ( Fig.…”
Section: Levels Of Mrnas Of Specific Gene Functional Categories Corrementioning
confidence: 92%
See 1 more Smart Citation
“…S1) versus their median transcription rate (TR, A-B), total [mRNA] (RA, C-D) and the degradation rate constant (k d , E-F) of their transcriptomes (see 15 other stresses show a positive correlation between TR and GR ( Fig. 2A), rather like that observed under steady-state conditions (see 18 ). On the contrary, the k d profiles show a positive correlation with iGR in all the stress responses ( Fig.…”
Section: Levels Of Mrnas Of Specific Gene Functional Categories Corrementioning
confidence: 92%
“…8 This regulatory behavior of respiration-related genes is specific for Crabtree-positive yeasts, 17 such as S. cerevisiae, because of the specialized evolved physiology of these organisms. 16,18 It is noteworthy that the way to achieve the correlation with GR differs. On the one hand, the ribosome-related and ESR-up genes vary their mRNA levels by changing their synthesis rates.…”
Section: Levels Of Mrnas Of Specific Gene Functional Categories Corrementioning
confidence: 99%
“…Early evidence for changes in gene regulation among fungi came from transcriptional profiling studies comparing S. cerevisiae, S. pombe and C. albicans [13][14][15]. Furthermore, predictions of cis-regulatory sequences, and meta-analyses of gene co-expression revealed that transcription networks have a great deal of flexibility [4,[16][17][18]. A well characterized example of comparative genomics applied to gene expression evolution is mating type identity that is controlled by distinct circuits with identical logic in S. cerevisiae and C. albicans [19 ].…”
Section: Introductionmentioning
confidence: 99%
“…More precisely, the goal is to understand which GRN properties improve the evolvability of living organisms. Some properties have already been highlighted in several articles [11][12][13]. Algorithms have been created to take advantage of them as Artificial Ontogeny [14] or lately PBGA [15].…”
Section: Existing Methodsmentioning
confidence: 99%